بررسی میزان موفقیت بخش دندانپزشکی کودکان دانشکده دندانپزشکی مشهد در آموزش مهارتهای بالینی از دیدگاه دانشجویان - حسین نعمت اللهی; لیلا رضیئی; راضیه خان محمدی; حجت شکیب (Mashhad University of Medical Sciences, 2013)
Introduction: Periodic evaluation of educational programs provides insight into the course and teaching effectiveness. Effective evaluation provides valuable information, which contributes to both student's and course success. The purpose of this study was to evaluate the success of pediatric dentistry department at Mashhad dental school in clinical education from students' perspectives. Materials & Methods: This cross-sectional study was conducted on 116 fifth and sixth grade undergraduate dental students in pediatric dentistry at Mashhad dental school. A questionnaire including 21 multiple choice questions about 7 parts of clinical skills in pediatric dentistry was given to each student. Data were analyzed by Mann-Whitney in SPSS software. Results: According to the study results, among 7 different clinical skills in pediatric dentistry including: examination, behavior management, prevention, injection, restoration, pulp treatment and space management, the highest success rate of pediatric dentistry department was in prevention and injection and the lowest success rate in space management and behavior control. Furthermore, from the students' perspective, male students compared to female students mentioned a higher rate of success in choosing the type of restoration material for pediatric dentistry department (P=0. 041). Conclusion: This study showed that the students' self-reported clinical skills in different parts of pediatric dentistry has been adequate. Students reported a lack of confidence in "behavior management" and "space management" which warrants greater emphasis in the undergraduate curriculum.